Elaboración de licor añejo con residuo de cascarilla y almendra de cacao nacional (Theobroma cacao L.). - Hidalgo Trejo, Guadalupe Cecibel (2017)
The present investigation had as aim evaluate the use of residues of husk and almond of national cocoa adding in different concentrations to the alcohol etílico rectified for the obtaining of old liquor with chemical and sensory acceptable characteristics. The design factorial secondhand was completely at random (DCA), with 3 repetitions, where the factors in study 2 were arranged in form bifactorial x 2 (Factor To = Residues of husk and almond of brown cocoa and without toasting; Factor B = Levels of residues 250 g and 500 g). The obtained information was analyzed in the statistical software SPSS, determining in the first instance the normal distribution or not of the brought values, using the test of Kolmogorov-Smirnov with 5 % of probability. Verifying that the information of the experimentation is not distributed in a normal way, the test was in use not paramétrico of Friedman, which threw as result that: the chemical variables analyzed by means of gas chromatography significant difference between treatments was not detected. On the contrary, and after observing the ADEVA in the sensory evaluation and that the attributes were analyzed intensity of color, smell, flavor to cocoa and preference was established as better treatment to the T2 that corresponds to brown residues of husk and almond of National cocoa 500 g.